Asymmetric septal hypertrophy and propranolol treatment in a case of Ullrich-Noonan syndrome. Issue 5 (November 1979) - Jackson, G; Anand, I S; Oram, S
Abstract : A 4-year-old boy with the Ullrich-Noonan syndrome is described. Asymmetric septal hypertrophy was diagnosed by echocardiography and confirmed at cardiac catheterisation. The aortic subvalvar gradient was reduced from 56 mmHg to 10 mmHg with intravenous propranolol. Relatives of patients with the syndrome should be screened by echocardiography in the hope that the early detection of asymmetric septal hypertrophy and its treatment with propranolol may reduce the likelihood of sudden death.